IDENTIFYING AND PRIORITIZING MARKETING PROBLEMS IN IRAN’S POULTRY INDUSTRY - Seyyedeh Mahsa Hosseini; Arash Hajikarimi (International Journal of Management Studies)
The marketing of poultry products is a critical component of all production systems. Given the importance of the poultry industry in Iran and the marketing challenges it faces, this research aims to identify and prioritize the marketing problems within the industry. Using the Delphi technique, 15 experts from the poultry industry helped identify the main factors causing marketing issues in poultry units. These factors were then ranked according to their importance using the AHP method. The findings classified the main marketing problems into six categories: product, price, supply, promotion, resources, and structure. The "resources" category emerged as the highest priority, while "promotion" was deemed the lowest. Among the sub-indicators, the lack of government support and inadequate facilities from banks and related organizations ranked the highest priority, whereas insufficient advertising for chicken meat ranked the lowest. The most important innovation of this research lies in its comprehensive ranking and prioritization of marketing problems specific to the poultry industry in Iran, an area that previous research has not yet explored.